Analysis of the impact of vlog news media form shaping on audience psychological immersion based on psychological experience process - He, Jingfan; Mohammad Razi, Siti Aishah; Ahmad Ghazali, Akmar Hayati (Cambridge University Press, 2023)
Background: How to enhance the psychological immersion of the audience is a major concern for the media at this stage. The psychological immersion of the audience not only affects the communication effect and influence of the media but also brings a more positive experience of reality to the audience. This project, therefore, analyses the psychological immersion of the audience based on the psychological experience process of shaping the media form of Vlog news. Subjects and Methods In this research, 228 college students were selected as the subjects of the experimental research. The mean age was 21.12±1.67 years, with 146 male students and 82 female students. The general demographic characteristics of all subjects were counted before the experiment and there were no significant differences (P > 0.05). All subjects were divided into a control group and a research group in a completely randomized manner. The control group disseminated news through traditional means, while the research group used a Vlog news medium based on a psychological experience process to disseminate news. The immersion scale was assessed using the Igroup Presence Questionnaire (IPQ), which consists of 13 items, with questions 1-5 on the spatial presence (SP) dimension, questions 6-9 on the involvement (INV) dimension, and questions 10-13 on the reality (REAL) dimension. Each item was scored on a scale of 0 to 6, with 0 indicating total disagreement and 6 indicating total agreement. Results: On the IPQ scale, the mean score of SP dimension was 3.12 ± 0.34 in the control group and 4.87 ± 0.42 in the research group, with a significant difference between the two groups (P < 0.05); the mean score of INV dimension was 2.53 ± 0.36 in the control group and 4.71 ± 0.38 in the research group, with a significant difference (P < 0.05); the score of REAL dimensions was 2.98 ± 0.28 in the control group and 4.52 ± 0.41 in the research group, with a significant difference. and 4.52 ± 0.41 in the research group, with a significant difference (P < 0.05).